SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-3551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Wide Tires and Trailer Aerodynamics on Fuel Economy and NOx Emissions of Class 8 Line-Haul Tractor-Trailers

Abstract: We hypothesize that components designed to improve fuel economy by reducing power requirements should also result in a decrease in emissions of oxides of nitrogen (NOx). Fuel economy and NOx emissions of a pair of class 8 tractor-trailers were measured on a test track to evaluate the effects of single wide tires and trailer aerodynamic devices. Fuel economy was measured using a modified version of SAE test procedure J1321. NOx emissions were measured using a portable emissions monitoring system (PEMS). Fuel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…However, battery electric and fuel cell trucks are exhaust emission free and are the cleanest options for the port drive and the urban drive applications. Compared to conventional Class 8 diesel trucks, conventional LNG-SI trucks have no apparent benefit in terms of CO 2 …”
Section: Simulations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, battery electric and fuel cell trucks are exhaust emission free and are the cleanest options for the port drive and the urban drive applications. Compared to conventional Class 8 diesel trucks, conventional LNG-SI trucks have no apparent benefit in terms of CO 2 …”
Section: Simulations and Discussionmentioning
confidence: 99%
“…Three approaches can be used to improve the fuel economy and/or reduce GHG emissions of heavy-duty trucks: non-electrification efficiency-improving technologies on conventional powertrains and vehicles [1][2][3], hybrid powertrain technologies [3][4], and the substitution of natural gas, electricity or hydrogen for diesel fuel [5][6]. All of these approaches have the potential to reduce GHG emissions from the transportation sector.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the engine performance is also costly for a Hachimi Fellouah 3 FE-12-1377 production vehicle. Reducing the aerodynamic drag has become an important improvement avenue since it allows increasing the fuel economy of the vehicle without adding any weight or without introducing any expensive technologies [2,3]. Moreover, the internal study also showed a dissipation force distribution in a World Motorcycle Test Cycle (WMTC) of 32 % for the rolling resistance drag and 68 % for the aerodynamic vehicle total drag.…”
Section: Introductionmentioning
confidence: 90%
“…Other truck applications with less mass and more frequent stops will have less efficiency gain. Replacing conventional dual tires with wide-base single tires can decrease fuel consumption by 1-11% in the nearterm 2015-2020 timeframe (NAS 2010;Franzese et al 2010;Bachman et al 2005;ATA 2008). Other strategies to reduce rolling resistance involve ensuring that tires are always properly inflated through the use of tire pressure monitoring systems automated tire inflation systems, and nitrogen tire inflation.…”
Section: Rolling Resistancementioning
confidence: 99%